Media Pembelajaran Miniatur Peta Kontur 3D bagi Siswa SMK Teknik Geospasial - Pratiwi, Henny; Isnandar, Isnandar; Ichwanto, Muhammad Aris Ichwanto (Universitas Nahdlatul Ulama Blitar, 2024)
The geospatial engineering skills program is a program that focuses on understanding surveying and mapping techniques. At SMK Negeri 1 Singosari in Cartography lessons for class X, learning uses conventional media and 2D printed maps, so efforts are needed to encourage active participation of students. This research aims to develop fun learning media for class X Geospatial Engineering students at SMK Negeri 1 Singosari. The research model applied in developing 3D contour map learning media is Research and Development. The research and development model is carried out using the ADDIE model. The resulting product is a miniature 3D contour map for class X cartography learning in Geospatial Engineering. The contour chosen in this media is the contour of the Mount Bromo area. This miniature 3D contour map media can be accessed using barcodes on Google Earth. The results of the assessment by material experts, media experts, small group and large group students showed a very good category. The learning media developed has advantages and disadvantages. The advantages of learning media are that it includes learning objectives, is equipped with access to the Google Earth application, and is equipped with guidelines on how to read 3D contour maps. Meanwhile, the weakness of this learning media is that it is large.Â